(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1989)
A new species of Limatula is erected. The material derives from clayey silt cropping out near Gravina in Puglia that represents the regressive ﬁnal phase of the Pleistocene "Gravina Clay" Formation.